Efeito do desbalanço genético e farmacológico do metabolismo oxidativo em indicadores de fertilidade masculina - Costa, Felipe (2016)
Previous studies indicate that changes in oxidative metabolism may play a role in reproductive success. Manganese-dependent superoxide dismutase enzyme (SOD2), a key in the oxidative balance, presents a genetic variation Val16Ala-SOD2 that leads to a change in its efficiency causing an imbalance between the superoxide (S) and hydrogen peroxide (HP) levels of Cells. Studies have suggested that both homozygous genotypes (AA-VV) cause an S-HP imbalance associated with the risk of various chronic diseases, and interfere with female reproductive success. Thus, the objective of this work was to investigate the effect of the genetic imbalance caused by the polymorphism Val16Ala-SOD2 and pharmacological induced by the treatment with paraquat in oxidative metabolism and in male fertility indicators. For the in vitro analysis of the impact of the S-HP imbalance caused by the pharmacological action of paraquat, a method of quantification of the levels of cfDNA in the seminal plasma was conducted by fluorimetry using the DNA Picogreen. The second protocol investigated the association between the Val16Ala- SOD2 polymorphism with changes in the male fertility parameters determined by the WHO, by evaluating the association of this polymorphism with high levels of cfDNA and markers of oxidative stress in seminal plasma. Semen samples were obtained from healthy volunteers or from surplus samples used to perform sperm in laboratory clinical analyzes, the samples were processed and analyzed in the Biogenomic Laboratory, through spectrophotometric and molecular tests. The results showed a significant association between elevated levels of cfDNA and altered fertility parameters in semen, such as: low viability, changes in motility and sperm morphology. In vitro complementary analysis confirmed that high levels of S causes oxidative stress and decrease sperm viability. These results corroborated the hypothesis that cfDNA levels could be markers of general sperm quality and oxidative stress.